ANALYSIS OF LOAD CAPACITY AND TEMPERATURE FIELD OF SPHERICAL HYBRID SLIDING BEARINGS (MT) - XUE Hao; SHEN JingFeng; QIN Wei; CHENG Pan; ZHU Rui (Jixie qiangdu)
The oil film temperature of the spherical hybrid sliding bearings would increase due to the friction and shear of the lubricating oil at high speed or super high speed, which leads to the thermal deformation of bearing and rotor. As a result, the deformation seriously affects the rotation accuracy of the spindle, because it is in the same order of magnitude as the oil film thickness. Therefore, the fluid lubrication mathematical model is established by taking the spherical hybrid sliding bearings with orifice throttling mode as the research object, and the Reynolds equation and energy equation of lubricating oil film are derived. The pressure distribution and temperature distribution of oil film of the spherical hybrid sliding bearings are calculated by combining the finite difference method and relaxation iteration method. The influence of working parameters on bearing capacity and oil film temperature rise was investigated. The results show that the oil film shear effect is stronger and the temperature rise increases with the increase of rotating speed and the decrease of oil film thickness. When the speed is 3 000 r/min and the oil film thickness is 28 μm, the maximum temperature rise of the bearing is 18.65 K higher than that of 1 000 r/min. When the speed is 3 000 r/min and the oil film thickness is 20 μm, the maximum temperature rise of the bearing is 27.685 K higher than that of the oil film thickness of 28 μm.